Prise de notes et attention en début d’apprentissage de l’interprétation consécutive — une expérience — démonstration de sensibilisation - Gile, Daniel (Meta, 1991)
AbstractAs an awareness-heightening exercise, taped speeches containing proper nouns were played back to two groups of 7 interpretation students at ISIT: members of a group A were instructed to listen carefully in view of a consecutive interpretation of the speeches and to note down any names and figures. Members of group B were instructed to listen carefully and take notes in preparation for consecutive interpretation. The numbers of names correctly noted, incorrectly notes and not noted at all in the two groups were computed and comparisons made.